Pathways to Better Nutrition in South Asia : Evidence on the Effects of Food and Agricultural Interventions - Dizon, Felipe (Elsevier, 2021)
In South Asia, nearly half a billion people are malnourished. This paper examines the links of food and agriculture with nutrition in South Asia, with the goal of informing policy to reduce hunger and malnutrition in the region. We investigate pathways including public food transfer programs, agricultural diversification, and different methods of food fortification. We find that public food transfer programs, used to make food available and affordable to poor households, are often unable to significantly protect or promote nutrition. But several supply-side food and agricultural interventions show promise in improving nutrition, although their effects have yet to be well identified. These include the cultivation of home gardens, animal agriculture, and use of biofortification and post-harvest fortification. All these efforts to reduce hunger and malnutrition will be futile, however, without parallel efforts to mitigate rising challenges in the region, including those posed by climate change, urbanization, food loss and food waste, and food safety hazards.